Rheology of surface granular flows - Orpe, Ashish V.; Khakhar, Devang V. (Journal of Fluid Mechanics, 2007)
Surface granular flow, comprising granular material flowing on the surface of a heap of the same material, occurs in several industrial and natural systems. The rheology of such a flow was investigated by means of measurements of velocity and number-density profiles in a quasi-two-dimensional rotating cylinder, half-filled with a model granular material – monosize spherical stainless-steel particles. The measurements were made at the centre of the cylinder, where the flow is fully developed, using streakline photography and image analysis. The stress profile was computed from the number-density profile using a force balance which takes into account wall friction. Mean-velocity and root-mean-square (r.m.s.)-velocity profiles are reported for different particle sizes and cylinder rotation speeds. The profiles for the mean velocity superimpose when distance is scaled by the particle diameter d and velocity by a characteristic shear rate and the particle diameter, where βm is the maximum dynamic angle of repose and βs is the static angle of repose. The maximum dynamic angle of repose is found to vary with the local flow rate. The scaling is also found to work for the r.m.s. velocity profiles. The mean velocity is found to decay exponentially with depth in the bed, with decay length λ = 1.1d. The r.m.s. velocity shows similar behaviour but with λ = 1.7d. The r.m.s. velocity profile shows two regimes: near the free surface the r.m.s. velocity is nearly constant and below a transition point it decays linearly with depth. The shear rate, obtained by numerical differentiation of the velocity profile, is not constant anywhere in the layer and has a maximum which occurs at the same depth as the transition in the r.m.s. velocity profile. Above the transition point the velocity distributions are Gaussian and below the transition point the velocity distributions gradually approach a Poisson distribution. The shear stress increases roughly linearly with depth. The variation in the apparent viscosity η with r.m.s. velocity u shows a relatively sharp transition at the shear-rate maximum, and in the region below this point the apparent viscosity η ∼ u−1.5. The measurements indicate that the flow comprises two layers: an upper low-viscosity layer with a nearly constant r.m.s. velocity and a lower layer of increasing viscosity with a decreasing r.m.s. velocity. The thickness of the upper layer depends on the local flow rate and is independent of particle diameter while the reverse is found to hold for the lower-layer thickness. The experimental data is compared with the predictions of three models for granular flow.

Characterizing the nanoclay induced constrained amorphous region in model segmented polyurethane-urea/clay nanocomposites and its implications on gas barrier properties - Rath, Sangram K.; Sudarshan, Kathi; Bhavsar, Rupesh S.; Kharul, Ulhas K.; Pujari, Pradeep K.; Patri, Manoranjan; Khakhar, Devang V. (Physical Chemistry Chemical Physics, 2016)
There has been an increasing recognition of the fact that purely geometric factors associated with clay platelet dispersion in a polymer matrix cannot adequately explain the barrier properties of polymer/clay nanocomposites. The objective of the present work is to understand the nanoclay induced structural changes in a polyurethane-urea matrix and clay dispersion at different length scales using segment-specific characterization techniques and implications of the same in gas barrier properties using He, N-2 and CO2 as probe molecules. Wide angle X-ray diffraction (WAXD) and positron annihilation life time spectroscopy (PALS) studies revealed nanoclay induced alterations in the chain packing of the amorphous soft segments of the polyurethane matrix at a molecular scale of a few Angstroms. The hard segment organization and the phase morphology of the nanocomposites, spanning length scales of several nanometers, were investigated by small angle X-ray scattering (SAXS), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Furthermore, the presence of a constrained amorphous region surrounding the nanoclay was confirmed from AFM, WAXD and PALS results. Several pertinent structural variables from the gas transport point of view were deduced from these characterization techniques to understand the effect of the barrier properties in tandem with the clay dispersion morphology.